Evidence of Hypertension in Healthy Children and Its Association with Body Composition and Aerobic Capacity - Tetteh, Aaron Azzu; Moses, Monday Omoniyi (Department of Physical Education, Sport, Health and Recreation, 2020)
Hypertension is mostly associated with adulthood and old age with little attention on children. This study provided evidence of hypertension in healthy children and its association with body composition and aerobic capacity (VO2max). 266 healthy children aged 8-11 years were recruited for the study. Blood pressure, heart rate, body mass index (BMI), basal metabolic rate (BMR), fat free mass, bone mass, visceral fat, total body water (TBW), and VO2max were measured. 18.79% were pre-hypertensive and 9.40% overweight at least, while 65.42% underweight. Correlation between blood pressure and maxVO2 was significant (P < 0.05). VO2max significantly correlate with body mass index (r = -.415, P < 0.05), fat mass (r = -.385, P < 0.05) negatively and visceral fat (r = -.267, P < 0.05) and positive with fat free mass (r =.385, P < 0.05) and bone mass (r =.077, P < 0.05). Gender differences were significant in BMR, TBW, VO2max and heart rate (P < 0.05). Evidence of hypertension in relatively healthy children is a clarion call to avert unprecedented decline in future life expectancy rate. Physical activity interventions are suggested antidotes to avert the risk factors of hypertension and excess body fat in children